Pengaruh Motivasi Terhadap Prestasi Kerja Anggota Kelompok Tani Di Desa Tridana Mulya Kecamatan Landono Kabupaten Konawe Selatan - Zainuddin Rela Iskandar; Awaluddin Hamzah; Muhammad Nurfadli (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
The purpose of this study was to analyze farmer motivation, farmer work performance and the influence of motivation on farmer work performance. This research was conducted in Tridana Mulya Village, Landono District, South Konawe Regency. The research sample was determined by the census method as many as 51 respondents. Data analysis used quantitative methods and qualitative descriptive methods based on the percentage of each research variable. The motivational factors consist of needs, expectations and the environment. While the aspects of work performance are analyzed based on the quality of work, responsibility and work discipline. The results showed that farmers in Tridana Mulya Village were motivated to improve their work performance. In general, the farmers' work performance was quite good. The motivation factor has a good enough effect on the work performance of the farmers in Tridana Mulya Village.